2017
DOI: 10.1016/j.physbeh.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Central GLP-1 receptor activation modulates cocaine-evoked phasic dopamine signaling in the nucleus accumbens core

Abstract: Drugs of abuse increase the frequency and magnitude of brief (1–3 s), high concentration (phasic) dopamine release events in terminal regions. These are thought to be a critical part of drug reinforcement and ultimately the development of addiction. Recently, metabolic regulatory peptides, including the satiety signal glucagon-like peptide-1 (GLP-1), have been shown to modulate cocaine reward-driven behavior and sustained dopamine levels after cocaine administration. Here, we use fast-scan cyclic voltammetry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 101 publications
(116 reference statements)
3
33
0
Order By: Relevance
“…For example, pharmacological activation of GLP-1Rs in the VTA, NAc core, and NAc shell reduces palatable food intake and body weight ( 144 ) and affects responses to drugs of abuse ( 145 147 ). Moreover, GLP-1R action within the VTA can alter phasic dopamine signaling as, in our laboratory, we demonstrated that LiCl-induced reductions in stimulated phasic dopamine release can be attenuated by GLP-1R blockade ( 58 ) and that ventricular injections of the GLP-1R agonist, exendin-4, can reduce cocaine-induced phasic dopamine signaling in the NAc core ( 148 ). These effects appear to be due, in part, to altered excitatory drive onto dopamine cell bodies as GLP-1R activation does not alter evoked NAc phasic dopamine release as measured in ex vivo brain slices ( 149 ).…”
Section: Homeostatic Signals Are Relayed To Mesolimbic Pathwaysmentioning
confidence: 99%
“…For example, pharmacological activation of GLP-1Rs in the VTA, NAc core, and NAc shell reduces palatable food intake and body weight ( 144 ) and affects responses to drugs of abuse ( 145 147 ). Moreover, GLP-1R action within the VTA can alter phasic dopamine signaling as, in our laboratory, we demonstrated that LiCl-induced reductions in stimulated phasic dopamine release can be attenuated by GLP-1R blockade ( 58 ) and that ventricular injections of the GLP-1R agonist, exendin-4, can reduce cocaine-induced phasic dopamine signaling in the NAc core ( 148 ). These effects appear to be due, in part, to altered excitatory drive onto dopamine cell bodies as GLP-1R activation does not alter evoked NAc phasic dopamine release as measured in ex vivo brain slices ( 149 ).…”
Section: Homeostatic Signals Are Relayed To Mesolimbic Pathwaysmentioning
confidence: 99%
“…The administration of leptin in the VTA decreases dopamine in the NAc (Fulton et al, 2006), possibly via a decrease in firing (Hommel et al, 2006) or excitatory synaptic transmission (Thompson & Borgland, 2013) onto dopamine neurons. Similarly, a GLP-1 receptor agonist, extendin-4, decreases excitatory synaptic transmission onto NAc-projecting dopamine neurons (Wang et al, 2015) and decreases dopamine release in the NAc (Fortin & Roitman, 2017b). Both intra-VTA leptin or GLP-1 agonists decrease food intake (Fulton et al, 2006;Hommel et al, 2006;Alhadeff et al, 2012;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that systemic and intra-VTA administration of EX4 can attenuate cue-induced cocaine seeking at doses that do not impact food intake (Hernandez et al, 2018). Central administration of EX4 has recently been shown to attenuate cocaine-induced phasic dopamine signaling in the NAc (Fortin and Roitman, 2017), possibly by increasing GABAA receptor mediated inhibition (Farkas et al, agonists impact reward-seeking behaviors by disrupting the motivational salience attributed to reward predictive incentive cues.…”
Section: Discussionmentioning
confidence: 99%
“…EX4 decreases both amphetamine-induced accumbal dopamine release and conditioned place preference (Egecioglu et al, 2013). ICV delivery of EX4 suppresses cocaine-induced phasic dopamine release in the NAc core, but not shell, with no effect on electrically stimulated release (Fortin and Roitman, 2017).…”
Section: Introductionmentioning
confidence: 98%